Preparation and electrical properties of bismuth tungstate solid electrolytes - Yuen, Mei Lian (2016)
Solid oxide fuel cells (SOFCs) are high efficiency power generators and operated at high temperature (1000 °C). Consequently, this high operating temperature may lead to many technological problems, such as material durability. Bismuth based electrolytes are able to perform higher ion conductivity than the current electrolytes (zirconia based) due to its intrinsic property (a quarter of oxygen sites for ions mobility). However, δ-Bi₂O₃ can exhibit high oxide ion conductivity at limited temperature range (730 °C to 825 °C). Introduction of WO₃ into Bi₂O₃ was conducted in an attempt to stabilize δ-Bi₂O₃ down to room temperature. Unfortunately, the produced WO₃ doped Bi₂O₃ materials with a general formula of (1-x)Bi₂O₃-xWO₃, (0.22 ≤ x ≤ 0.255), were unable to stabilize δ-Bi₂O₃. Eventually, these materials synthesized via conventional solid state method and mechanochemical method, respectively, were fully indexed on the tetragonal system with space group I41. Single phase material of Bi6.24W0.88O12, can be obtained at lower temperature with shorter durations through mechanochemical method. The tetragonal structure, Bi6.24W0.88O12, synthesised through mechanochemical method was obtained at 650 °C for 24 hours, while the conventional solid state method synthesized material required a higher temperature (700 °C) for longer duration (48 hours) to obtain a pure phase material. It must be highlighted that Bi6.24W0.88O12 did not undergo decomposition under the studied temperature range (room temperature to 910 °C) based on the XRD patterns from thermal stability experiment and data from thermogravimetric analysis (TGA). This behavior clearly indicated that Bi6.24W0.88O12 was a high stability material. Three vibration bands (ν(W-O-W), Bi-O and ν (W-O)) were noticed in spectra of Fourier-transform infrared (FT-IR) spectroscopy. Scanning Electron Microscopy (SEM) micrographs for pellets sintered at 900 °C illustrated greater grain size compared to pellets sintered at 700 °C. It was inferred that resistance of material could be reduced. X-ray Fluorescence (XRF) analysis recorded data with percentage of error below 5 %, hence, this validated that compositions material and gave a confidence of the current work results. Bi6.24W0.88O12 exhibited the best ionic conductivity among other solid solutions of (1-x)Bi2O3-xWO3, (0.22 ≤ x ≤ 0.255). Bi6.24W0.88O12 fabricated by mechanochemical method demonstrated the highest conductivity of 2.25 x 10-2 ohm-1cm-1 at 600 °C (average grain size of 12.46 μm to 48.16 μm) than conventional solid state route materials. It was also worthwhile to point out that a pure Bi6.24W0.88O12 ion conducting solid electrolyte without any electronic conduction was produced with ionic conductivity of 6 orders higher than the reported YSZ at 600 °C, elucidating a greater potential of Bi6.24W0.88O12 to be used as a material utilized in SOFC electrolytes applications. Doping was carried out on the Bi or W sites in Bi6.24W0.88O12 with selected dopants, including monovalent (Li+), divalent (Ca2+, Cu2+, Ni2+ and Zn2+), trivalent (Cr3+ and Y3+), tetravalent (Sn4+, Ti4+ and Zr4+), pentavalent (Sb5+, V5+, Nb5+ and Ta5+) and hexavalent (Mo6+) cations in order to investigate their effects on the electrical properties of doped Bi6.24W0.88O12 materials. All these dopants can be introduced into Bi6.24W0.88O12 with rather limited solid solution ranges. Ion vacancy, ionic potential and unit cell parameters of structure are the main factors that varying the conductivity of the doped materials. Bi6.24W0.68Nb0.20O11.900 was developed and achieved the highest oxide ion conductivity (2.96 x 10-2 ohm-1cm-1 at 600 °C) among other cation dopants. This doped material was 32 % more conductive than the undoped material. Therefore, it is important to point that this doped material could elevated the performance of SOFC. Nb particles (tiny particle) were homogeneously distributed over the surface ceramic of Bi6.24W0.68Nb0.20O11.900 as illustrated in SEM image.